Assessment of Musculoskeletal Disorders in Brick Workers Using an Ergonomic Approach - Pratiwi, Indah; Setyawan, Robi (Universitas Airlangga, 2024)
Introduction: This study focuses on micro, small, and medium enterprises (MSMEs) engaged in the manual production of bricks. Specifically, it addresses the repetitive tasks of hoeing, mixing clay, and lifting and carrying bricks, which are performed for prolonged periods. The aim is to assess and mitigate risk factors associated with these manual tasks that may lead to musculoskeletal disorders (MSDs). Methods: The study involved 75 male workers with an average age of 43.52 ± 11.02 years, an average work experience of 14.18 ± 10.43 years, and an average body mass index (BMI) of 23.73 ± 2.59. The workers' manual material handling (MMH) activities were evaluated using the Workplace Ergonomic Risk Assessment (WERA) and Key Indicator Method (KIM). Additionally, the Nordic Body Map (NBM) questionnaire was used to identify areas of the body where workers experience pain related to their tasks. Results: The WERA assessment identified ten activities with a medium risk level, necessitating further analysis. The KIM assessment revealed six activities with a very high risk level and four with high risk. Recommendations were made for four high-risk activities, specifically suggesting the redesign of material transport carts. This intervention has the potential to reduce injury risk scores by up to 50%. Conclusion: The combined use of the WERA and KIM methods proves effective in assessing MMH risk in brick-production MSMEs, offering insights for targeted ergonomic interventions.